Sarcoidosis Presenting as an Intraperitoneal Mass - John V. Brown III; Howard D. Epstein; Miles Chang; Bram H. Goldstein (Case Reports in Oncology, 2010)
Background: Sarcoidosis is an idiopathic, inflammatory condition primarily encountered within the lungs but very rarely identified in the peritoneum. Case Study: A 34-year-old woman presented with pleural effusion, ascites and an adnexal mass, indicative of ovarian cancer. Results: A biopsy revealed granulomas and lymphocytic infiltrate, consistent with sarcoidosis. The patient’s symptoms were resolved with corticosteroids. However, 2 years later, she developed another pelvic mass and underwent a diagnostic laparoscopy. Final pathology revealed granulomas and endometriosis, consistent with sarcoidosis. Conclusion: Since intraperitoneal sarcoidosis is extremely rare, the differential diagnosis is unlikely to include this condition in the context of presumptive ovarian cancer. However, in patients with a history of sarcoidosis, physicians should maintain a high index of suspicion to effectuate early detection and provide appropriate treatment.